Pembelajaran dengan Pendekatan Kontekstual untuk Meningkatkan Kemampuan Pemahaman Matematis - Muhsin Muhsin; Zulfa Razi (Universitas Syiah Kuala, 2018)
Mathematical comprehension ability is a very important initial ability possessed by students in the learning process of mathematics, especially in understanding mathematics. One important goal in learning mathematics is that the material taught to students is not as memorization, but with understanding students can understand the concept of mathematical material. Mathematical understanding is one of the goals of every material delivered by the teacher, because the teacher is the student's guide to achieving the expected concept. Therefore, it is very important to develop and improve the ability of students' mathematical understanding in the process of learning mathematics. This study aims to examine the enhancement of the ability of mathematical understanding between students who obtain learning with a contextual approach and students who obtain conventional learning. This research is an experimental study using a pre-test post-test control group design. The population in this study were students of class VIII MTsN 4 Pidie, Aceh in the 2018/2019 school year. Through purposive sampling, two classes were chosen in parallel, namely class VIII1 as the experimental class and VIII2 as the control class. The instrument used to collect research data is a mathematical comprehension ability test. The statistical test used is the t-test to analyze the data for increasing the ability of mathematical understanding. The results of the study showed that the improvement of students' mathematical comprehension ability who obtained contextual approach learning was better than students who received conventional learning.